(untitled) (Wallingford, 2007)
This book presents a series of review chapters on ecologically-based IPM. Topics covered range from the ecological effects of chemical control practices to the ecology of predator-prey and parasitoid-host systems.
Thâm cứu bảo vệ thực vật,IPM trong bảo vệ thực vật
Keywords: Agricultural pests,Insect pests,Plants, Protection of; Integrated control,Environmental aspects,Control,Environmental aspects